L'Ernesto, ovvero Il prigione di Umberto Saba - Prola, Dario (Acta neophilologica, 2015)
Privileged meeting point between Slavic, Latin and Germanic cultures, Trieste has always been a breeding ground of literal experiments, a place where the old meets the new, tradition modernity. Its natural creativity and receptivity is to be found in its flowing, open identity, in the absence of that weight that national institutions ascribe to monoethnic and national culture. Ernest, the uncompleted novel of Umberto Saba, an Italian poet native of Trieste, was written in 1953 just before dying and published in 1975. Its open and indefinite form still fascinates critics and readers. It is the late confession of Saba's conquer of his sexual and artistic identity, with the city of Trieste between nineteenth and twentieth century as background. In this Künstlerroman Nietzsche and Freud's lesson has been elevated by Saba's lyric strength and by a prose, which expressive style comes from the combination of literal Italian and the Triestine dialect. This article offers the analyses of the text through the definition of the concepts of undefinedness, intimacy and lightness in Umberto Saba's poetic.
Keywords: "Ernesto"; intimacy; intimnost; Italian literature; italijanska književnost; Künstlerroman; lahkotnost; lightness; nedefiniranost; novel; roman; Saba, Umberto, 1883-1957; Trieste; Trst; undefinedness